Imagination's afterlife: influences on and transformations of literary creative process within a Creative Practice PhD. Issue 1 (2nd January 2018) - Masson, Sophie
ABSTRACT: Professional authors of imaginative literature, whether fiction or non-fiction, follow creative processes that have been built from a mix of experience and instinct. These are specific and individual to each author, but have been established by them over time, and frequently in an informal, non-analytical, but nevertheless successful way. What happens when a professional author, used to such a process, undertakes the writing of a creative work within the framework of a PhD? What influences come to bear on the creative work from the analytical, academic part of the PhD project? Does creative process change? If so, how? And what impact might it be expected to have on the final work, and the author's continuing creative practice, even beyond the period of study? Drawing on interviews with writers who are undertaking or have recently completed a creative writing PhD, and with creative writing academics, the author of this paper, an established novelist and PhD student, examines the synergies between imagination and analysis within a higher degree research project, and how this affects the creative process itself.